Absorption kinetics of mercury (II) chloride into water and aqueous sodium chloride solution - Kho, F.; Pham, Gia (Elsevier, 2018)
Mercury has been reported to be naturally occurring trace contaminant in the oil and gas reservoirs. In this study, the absorption characteristic of mercury (II) chloride (HgCl2) in water and aqueous sodium chloride (NaCl) solution was investigated. The kinetic parameters of the reaction between HgCl2 and NaCl is reported for the first time. A semi-batch reactor is used in this work to investigate the absorption process. The solid vaporization method is applied to generate HgCl2 gas at different concentrations for this study. At the same hydrodynamic condition, the absorption flux of HgCl2 into water increases from 6.02 × 10−6 to 10.26 × 10−6 mol/m2.h when absorption temperature is increased from 298 to 333 K. Applying the two-film theory, the absorption of HgCl2 into water is controlled by the gas phase resistance. The mass transfer coefficient kG does not change with the HgCl2 concentration in the gas phase significantly, but is affected by the absorption temperature. For the case of absorption of HgCl2 into aqueous NaCl solution, the absorption flux increases with increasing NaCl concentration and absorption temperature. The mechanism of reaction between HgCl2 and NaCl is proposed and the reaction rate law follows second order; first order with respect to HgCl2 and Cl− with the reaction rate constant k2 = 1.09 X 10 9 exp (-123.32 kJ / mol_RT) m3/mol·s.